2018
DOI: 10.2174/1874325001812010525
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report: Custom Made Porous Titanium Implants in Revision: A New Option for Complex Issues

Abstract: Background: Bone loss management is considered one of the most difficult challenges for orthopaedic surgeon. In massive bone defects, few surgical options are available and they do not offer a reliable or optimal solution for knee reconstruction. Objective: The aim of this paper is to present and justify a new custom-made approach for complex metadiaphyseal bone defects management in knee revision surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Comparison has been made with several studies that showed lower and homogeneous stresses' distribution on porous implants when compared with traditional nonporous materials. 28,34,35 In addition to that, nowadays, a single component can be produced using 3D printing, enabling every aspect, and achieving high-dimensional accuracy in small geometries. Nowadays, several companies are using 3D printing for the increasing need for optimization and customization of medical devices in the orthopedic ¯eld.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison has been made with several studies that showed lower and homogeneous stresses' distribution on porous implants when compared with traditional nonporous materials. 28,34,35 In addition to that, nowadays, a single component can be produced using 3D printing, enabling every aspect, and achieving high-dimensional accuracy in small geometries. Nowadays, several companies are using 3D printing for the increasing need for optimization and customization of medical devices in the orthopedic ¯eld.…”
Section: Discussionmentioning
confidence: 99%
“…Such models can add improvements to the fixation inserting flanges to add screws in the ilium, ischium, and/or pubic bone. 6 Another advantage is to foresee the difficulties of insertion of the made-to-measure acetabular component. Ideally, these advantages lead to a shorter surgical time, management of bone defect issues, and implant stability in a separate way.…”
Section: Discussionmentioning
confidence: 99%
“…Tais modelos podem agregar melhorias à fixação, inserindo flanges para agregar parafusos no ílio, ísquio e/ou osso púbico. 6 Outra vantagem é antecipar dificuldades de inserção do componente acetabular feito sob medida. Idealmente, essas vantagens levam a um tempo cirúrgico mais curto e ao gerenciamento dos problemas de defeitos ósseos, e à estabilidade do implante separadamente.…”
Section: Discussionunclassified
“…Custom-made devices are a new and promising option in several complex surgical settings 4 . Burastero et al firstly reported the experience with custom porous titanium cones in complex knee revision surgery showing optimal short-term clinical and radiological outcomes 5 . These results are confirmed by Cherny et al 6 .…”
Section: Discussionmentioning
confidence: 99%